Privacy in the Age of Big Data - Saini, Shubhash Chandra; Sharma, Vinny; Verma, Vishakha (International Journal of Psychosocial Rehabilitation, 2020)
This study delves into the realm of Data Privacy within the Age of Big Data, providing a complete analysis of the demanding situations and feasible solutions associated with safeguarding privateness within the context of extensive datasets. In an era marked by way of the proliferation of big datasets, this research is pushed by using the imperative to apprehend, deal with, and mitigate the privacy worries springing up from the considerable collection, storage, and analysis of personal facts. The challenges in preserving records privateness within the context of Big Data are multifaceted. The sheer extent and style of statistics present bold hurdles, making it inherently challenging to put in force powerful privacy measures. Moreover, the interconnected nature of various datasets heightens the threat of re-identification, in which ostensibly anonymized statistics may be related to particular individuals. The ability for unauthorized get admission to, facts breaches, and the misuse of private facts in the age of Big Data poses an ongoing chance to character privacy rights. To counter these challenges, this research explores a variety of solutions geared toward preserving facts privateness while harnessing the blessings of large datasets. Encryption strategies, anonymization methods, and differential privateness techniques are scrutinized for their effectiveness in mitigating privacy dangers. The look at also delves into the position of strong governance frameworks and criminal policies to set up clear suggestions for the accountable dealing with of private facts inside Big Data environments. Furthermore, the research underscores the importance of technological improvements which include federated getting to know and homomorphic encryption, which permit records evaluation with out the want for raw facts sharing. These innovations offer promising avenues for preserving individual privateness whilst nevertheless deriving significant insights from big datasets. In essence, this look at contributes to the continued discourse surrounding information privacy inside the age of Big Data by providing a nuanced understanding of the challenges concerned and supplying possible answers. The effects of this studies goal to inform policymakers, corporations, and records practitioners on the essential importance of imposing effective privateness measures to make sure the responsible and ethical use of sizable datasets in modern facts-driven landscapes.